Mass Disaster in Bangladesh: Forensic View (Bangladesh Medical Journal, 2009)
Achievements in all spheres of humans endeavour to create a better world and the progress they made over generations all can be wiped out in a twinkle of an eye. All can take in a violent disaster natural or unnatural. Bangladesh, one of the least developed country of the world, burdened with large population had been affecting by some form of natural disaster like flood, cyclone, tidal surges etc every year. These disasters were due to its geographical location and geophysical climate. On the other hand, unnatural disaster like plane crushes, fires, shipwrecks, railway and other transport accidents, bomb blast etc. are some times avoidable under some precautionary measures. The process of identification of the victim of disaster is one of the challenging problem for a forensic pathologist. Forensic investigator can contribute their role expertise and recommendations in collaboration with other agencies.   DOI: 10.3329/bmj.v37i1.3603 Bangladesh Medical Journal 37(1) 2008 19-20